The Impact of Regional Variation in Clinical Practice on Thyroid Cancer Diagnosis: A National Population-Based Study. Issue 1 (21st January 2020) - Decallonne, Brigitte; Van den Bruel, Annick; Macq, Gilles; Elaut, Nathalie; De Schutter, Harlinde
Abstract : Objective: Regional variation in thyroid cancer incidence in Belgium, most pronounced for low risk cancer, was previously shown to be related to variation in clinical practice, with higher thyroid surgery rates and lower proportions of preoperative fine-needle aspiration (FNA) in regions with high thyroid cancer incidence (period 2004–2006). The objective of this study was to investigate regional thyroid cancer incidence variation in relation with variation in thyroid surgery threshold in a more recent Belgian thyroid cancer cohort. Methods: A population-based cohort of thyroid cancer patients that underwent a (near) total thyroidectomy in the period 2009–2011 ( n = 2, 329 patients) was identified and studied by linking data from the Belgian cancer registry and the Belgian health insurance companies, and case-by-case study of the pathology protocols. The execution of preoperative FNA and the thyroid resection specimen weight were compared between high and low thyroid cancer incidence regions. Thyroid weight in the pT1a-restricted group was studied as a proxy for surgical threshold for benign nodular goiter. Furthermore, time trend analyses were performed for the execution of FNA for the period 2004–2012. Results: Although a lower proportion of FNA in the high thyroid cancer incidence region persisted in the period 2009–2011 (41.2% [31.9–50.9] vs. 72.9% [64.9–79.7] in the low-incidence region (LIR), p < 0.001), a positive time trend was observed for the period 2004–2012. The median thyroid surgical specimen weight was lower in the high incidence region compared to the LIR (27.0 g [IQR 18.0–45.3] vs. 36.0 g [IQR 22.0–73.0], p < 0.0001), and this finding was corroborated in the pT1a-restricted group. Conclusion: Interregional differences in use of FNA and surgical thyroid specimen weight are consistent with an inverse relation between thyroid cancer incidence and thyroid surgery threshold, carrying risk for overdiagnosis.